Applicability in forensics and population genetics: developmental validation of Ingenomics™ Y Profiler STR kit - Shivkant Sharma; Rajendra V. E. Chilukuri; Vikash Sharma; Kapil Dev; Anita Pundir; Danish Qazi; Deepika Tiwari; Rubina Mohammed; Umema Ahmad; Jaison Jeevan Sequeira; Gyaneshwer Chaubey (The Nucleus, 2026)

Developmental validation of the Ingenomics™ AutoProfiler STR system: a 6-dye STR multiplex kit for forensic DNA applications - Shivkant Sharma; Rajendra V. E. Chilukuri; Rhea Shetkar; R. K. Kumawat; Vivek Sahajpal; Shivani Dixit; B. K. Mohapatra; Dhirendra Singh Yadav; Kapil Dev; Rubina Mohammed; Umema Ahmad; Krishna Mani Yadav; et al. (The Nucleus, 2026)

Correlation, Path Coefficient and Genetic Diversity Analysis in EMS Induced Cultivars of Ashwagandha [Withania somnifera (L.) Dunal] - Puja Kumari; Tara Chandra Ram; Nashra Aftab; Himanshu Kumar Kushwaha; Manju Singh; Kapil Dev; Birendra Kumar (Biochemical Genetics, 2026)

Plant-derived indole alkaloids as opioid receptor modulators - Shraddha Srivastava; Arti Shukla; Girendra Yadav; Kapil Dev (Natural Product Research, 2026)

A new sesquiterpene lactone isolated from Ainsliaea smithii and cytotoxic activity against the A549 cancer cell line - Kishan Singh; Kaveri R. Washimkar; Divya Kushwaha; Madhav Nilakanth Mugale; Kapil Dev (Natural Product Research, 2026)

Cheilanthenetetraol, a sesterterpenoid isolated from Aleuritopteris bicolor with anti-hepatocellular carcinoma and anti-inflammatory activity - Kishan Singh; Smriti Verma; Rida Siddiqui; Monazza Israr; Dnyaneshwar Umrao Bawankule; Madhav Nilakanth Mugale; Kapil Dev (Journal of Natural Medicines, 2026)

Comparative chemical profiling, antimicrobial potential, and integrative network pharmacological assessment of Pinus roxburghii Sarg. essential oils - Kapil Dev; Ritesh Sharma; Sanjeev K. Sharma; Aparna Maitra Pati; Vijai K. Agnihotri (Natural Product Research, 2025)

Baicalein isolated from Oroxylum indicum acts as a potent µ- and κ-opioid receptor antagonist agent via the reversal of agonist-mediated cAMP inhibition - Kishan Singh; Anubhav Yadav; Sana Khan; Arti Shukla; Maksood Alam; Ashutosh Kumar Verma; Neerja Tiwari; Feroz Khan; Prem Narayan Yadav; Kapil Dev (Natural Product Research, 2025)

miR-101-3p overexpression suppresses NSCLC progression through Immune-Related gene CALCRL regulation and lncRNA NEAT1 axis - Gulnaz Tabassum; Shweta Arora; Prithvi Singh; Mohd Mohsin; Salman Khan; Aman Khan; Ravins Dohare; Kapil Dev; Mansoor Ali Syed (Molecular Biology Reports, 2025)

Diversity and Functional Characterization of Endophytes in Two Contrasting Cultivars of Ocimum sanctum: Insights from Culture-Based and Metagenomic Approaches - Rahul Kumar Gupta; Shiwangi Singh; C S Chanotiya; Kapil Dev; Prabodh Kumar Trivedi; Akanksha Singh (Journal of Plant Growth Regulation, 2025)

Stability Analysis of Darcy–Bénard Convection Subjected to Time-Dependent Heating Using an LTNE Model - Kapil Dev; Chunendra K. Sahu (Transport in Porous Media, 2025)

Determining the best timing of insemination based on salivary fern pattern and its association with conception in buffalo - Aashirbad Pokharel; Gokarna Gautam; Shatrughan Shah; Kapil Dev Yadav; Mourad Rekik; Deka Ram Pratim; Padmakumar Varijakshapanicker; Bhuminand Devkota (Animal Reproduction Science, 2025)

Synergistic effect of molybdenum and Rhizobium on growth and yield of vegetable cowpea (Vigna unguiculata (L.) Walp.) - Monu Kumari; Nitin B. Patel; Kapil Dev Ameta; Akshay Kumar Yogi; Harshit Kumar; Ayushi Jain (Vegetos, 2025)

Characteristics of the electron beam outside the applicator in an Elekta Versa HD Linac - Kapil Dev Maharaj; Simon Goodall; Mahsheed Sabet; Joshua Dass; Mounir Ibrahim; Talat Mahmood; Pejman Rowshanfarzad (Physical and Engineering Sciences in Medicine, 2025)
Radiotherapy is an essential component of cancer treatment, but healthy tissues can be exposed to out-of-field doses, potentially causing adverse effects and secondary cancers. This study investigates peripheral doses outside the electron beam applicator in an Elekta Versa HD linear accelerator. Peripheral doses outside an electron applicator were measured using 6, 9, and 12 MeV beams at their respective maximum dose depths while maintaining a 100 cm source-to-surface distance. Measurements employed EBT3 films within Plastic Water DT phantoms. The influence of field size on penumbra width and peripheral doses were examined using various cutouts (6 × 6 cm², 10 × 10 cm², and a 5 cm diameter circle) within a 10 × 10 cm² applicator, with gantry and collimator angles set to 0 degrees. Additionally, the impact of collimator angles on penumbra width and peripheral doses was explored, enhancing the understanding of dose distribution. Measured profiles were also compared with those calculated using Monaco treatment planning system. Findings showed that both penumbra width and peripheral dose values increased with energy across different field sizes and collimator angles. Root Mean Square Deviation (RMSD) analysis indicated deviations of 1.8 mm for penumbra and 1.1% for peripheral doses between measured profiles and Treatment Planning System (TPS) predictions for all field sizes. Peripheral doses remained below 5% of the maximum dose at distances ranging from 10 to 15 mm away from the field edges, indicating acceptable tolerance levels (ICRU report 24). However, further dose reduction may be possible with additional shielding to keep doses as low as reasonably achievable. This study highlights the critical importance of considering peripheral doses in radiotherapy, emphasizing the need to evaluate the impact on healthy tissues outside the primary treatment area to ensure patient safety and mitigate long-term treatment-related side effects. The findings underscore the necessity of implementing appropriate measures to minimize peripheral doses.

Hallmarks of diabetes mellitus and insights into the therapeutic potential of synergy-based combinations of phytochemicals in reducing oxidative stress-induced diabetic complications - Mohammad Irfan Dar; Anu Gulya; Sageer Abass; Kapil Dev; Rabea Parveen; Sayeed Ahmad; Mohammad Irfan Qureshi (Natural Product Research, 2025)

Comparative chemical profiling, antimicrobial activity of Cyclospermum leptophyllum (Pers.) Sprague ex Britton and P. Wilson essential oil and evaluation of their integrative network pharmacology - Kapil Dev; Ritesh Sharma; Sanjeev K. Sharma; Aparna Maitra Pati; Vijai K. Agnihotri (Natural Product Research, 2025)

Psiguanol, a novel α-pyrone derivative from Psidium guajava leaves and vasorelaxant activity in rat aorta cells through intracellular cGMP-dependent opening of calcium-activated potassium channels - Shraddha Srivastava; Divya Mishra; Rohit Bisht; Kumari Savita; Kishan Singh; Poonam Rani; Debabrata Chanda; Kapil Dev (Natural Product Research, 2025)

Cost-effective synthesis route for ultra-high purity of Ti3AlC2 MAX phase with enhanced performance of Ti3C2Tx MXene and MXene/NiO composite for supercapacitor application - Kapil Dev Verma; Kamal K. Kar (Chemical Engineering Journal, 2025)

Therapeutic importance of Kigelia africana subsp. africana : an alternative medicine - Zahra Abbas; Saad Mustafa; Mohd Faisal Khan; Mohammad Aasif Khan; Sheersh Massey; Kapil Dev; Asifa Khan; Shabana Parveen; Syed Akhtar Husain (Natural Product Research, 2024)

Room temperature benzene gas sensing properties based on Sr-substituted ceria oxide nanopetals - V. Manikandan; Ankit Kadian; Kapil Dev; S. Annapoorni (Journal of Environmental Chemical Engineering, 2024)

Allelopathic weed management in wheat (Triticum aestivum L.) through essential oil emulsions and aqueous botanical extracts-based novel bioherbicides - Pooja Maurya; Nihal Dwivedi; Abdul Mazeed; Dipender Kumar; Birendra Kumar; Chandan Singh Chanotiya; Kapil Dev; Priyanka Suryavanshi (Journal of Plant Diseases and Protection, 2024)

Detection of Expanded Reformed Geographical Area in Bi-temporal Multispectral Satellite Images Using Machine Intelligence Neural Network - Mohan Singh; Kapil Dev Tyagi (Journal of the Indian Society of Remote Sensing, 2022)

Dietary Lactobacillus acidophilus and Mannan-Oligosaccharides Alter the Lipid Metabolism and Health Indices in Broiler Chickens - Kapil Dev; Jubeda Begum; Avishek Biswas; Jyoti Kannoujia; Nasir Akbar Mir; Joyshikh Sonowal; Rajiv Kant; T. Narender (Probiotics and Antimicrobial Proteins, 2021)

Cloud fraction biases in CALIPSO simulators of CMIP5 models over India - Kapil Dev Sindhu; Ram Ratan (Theoretical and Applied Climatology, 2020)

Feeding value of rice distiller’s dried grains with solubles as protein supplement in diet of laying hens - Sneh Lata Gupta; Pramod K. Tyagi; Nasir Akbar Mir; Kapil Dev; Jubeda Begum; A. B. Mandal; Praveen K. Tyagi (Tropical Animal Health and Production, 2020)

Storm characteristics and precipitation estimates of monsoonal clouds using C-band polarimetric radar over Northwest India - Kapil Dev Sindhu; G. S. Bhat (Theoretical and Applied Climatology, 2019)

Detection of flavonoids from Spinacia oleracea leaves using HPLC-ESI-QTOF-MS/MS and UPLC-QqQ LIT -MS/MS techniques - Awantika Singh; Pratibha Singh; Brijesh Kumar; Sudhir Kumar; Kapil Dev; Rakesh Maurya (Natural Product Research, 2019)

Long-term cloud fraction biases in CMIP5 GCMs over India during monsoon season - Kapil Dev Sindhu; Sandeep Sahany (Theoretical and Applied Climatology, 2019)

New lignan glycosides from Cissus quadrangularis stems - Padam Kumar; Kapil Dev; Khushbu Sharma; Mahendra Sahai; Rakesh Maurya (Natural Product Research, 2019)

Effects of high fluoride content in livestock drinking water on milk samples of different cattle in endemic area of Pakistan: risk assessment for children - Tasneem Gul Kazi; Kapil Dev Brahman; Hassan Imran Afridi; Faheem Shah; Mohammad Balal Arain (Environmental Science and Pollution Research, 2018)

Evaluation of genetic and non-genetic factors on foot and mouth disease (FMD) virus vaccine-elicited immune response in Hardhenu (Bos taurus x Bos indicus) cattle - Manjeet; B. L. Pander; R. Sharma; S. S. Dhaka; Ankit Magotra; Kapil Dev (Tropical Animal Health and Production, 2017)

Phytochemical investigation of Kigelia pinnata leaves and identification of osteogenic agents - E. Ramakrishna; Kapil Dev; Priyanka Kothari; Ashish Kumar Tripathi; Ritu Trivedi; Rakesh Maurya (Medicinal Chemistry Research, 2017)

Simultaneously removal of inorganic arsenic species from stored rainwater in arsenic endemic area by leaves of Tecomella undulata: a multivariate study - Kapil Dev Brahman; Tasneem Gul Kazi; Hassan Imran Afridi; Jameel Ahmed Baig; Muhammad Ishaque Abro; Sadaf Sadia Arain; Jamshed Ali; Sumaira Khan (Environmental Science and Pollution Research, 2016)

Toxic Risk Assessment of Arsenic in Males Through Drinking Water in Tharparkar Region of Sindh, Pakistan - Kapil Dev Brahman; Tasneem Gul Kazi; Hassan Imran Afridi; Sadaf Sadia Arain; Atif Gul Kazi; Farah Naz Talpur; Jameel Ahmed Baig; Abdul Haleem Panhwar; Mariam Shezadi Arain; Jamshed Ali; Mohammad Balal Arain; Naeemullah (Biological Trace Element Research, 2016)

Correlation of cadmium and aluminum in blood samples of kidney disorder patients with drinking water and tobacco smoking: related health risk - Abdul Haleem Panhwar; Tasneem Gul Kazi; Hassan Imran Afridi; Salma Aslam Arain; Mariam Shahzadi Arain; Kapil Dev Brahaman; Naeemullah; Sadaf Sadia Arain (Environmental Geochemistry and Health, 2016)

Erratum to: Preconcentration and determination of lead and cadmium levels in blood samples of adolescent workers consuming smokeless tobacco products in Pakistan - Sadaf Sadia Arain; Tasneem Gul Kazi; Hassan Imran Afridi; Kapil Dev Brahman; Naeemullah; Sumaira Khan; Abdul Haleem Panhwar; Muhammad Afzal Kamboh; Jamil R. Memon (Environmental Monitoring and Assessment, 2015)

Preconcentration and determination of lead and cadmium levels in blood samples of adolescent workers consuming smokeless tobacco products in Pakistan - Sadaf Sadia Arain; Tasneem Gul Kazi; Hassan Imran Afridi; Kapil Dev Brahman; Naeemullah; Sumaira Khan; Abdul Haleem Panhwar; Muhammad Afzal Kamboh; Jamil R. Memon (Environmental Monitoring and Assessment, 2015)

Assessment of selenium and mercury in biological samples of normal and night blindness children of age groups (3–7) and (8–12) years - Hassan Imran Afridi; Tasneem Gul Kazi; Farah Naz Talpur; Atif Kazi; Sadaf Sadia Arain; Salma Aslam Arain; Kapil Dev Brahman; Abdul Haleem Panhwar; Naeemullah Khan; Mariam Shazadi Arain; Jamshed Ali (Environmental Monitoring and Assessment, 2015)

Comparative evaluation of essential and toxic elements in the blood of kidney failure patients and healthy referents - Abdul Haleem Panhwar; Tasneem Gul Kazi; Hassan Imran Afridi; Salma Aslam Arain; Mariam S. Arain; Kapil Dev Brahman; Naeem Ullah; Jamshed Ali; Sadaf Sadia Arain (Environmental Monitoring and Assessment, 2015)

Evaluation of fresh and stored rainwater quality in fluoride and arsenic endemic area of Thar Desert, Pakistan - Kapil Dev Brahman; Tasneem Gul Kazi; Hassan Imran Afridi; Tahir Rafique; Jameel Ahmed Baig; Sadaf Sadia Arain; Naeem Ullah; Abdul Haleem Panhwar; Salma Arain (Environmental Monitoring and Assessment, 2014)

Determination of nickel in blood and serum samples of oropharyngeal cancer patients consumed smokeless tobacco products by cloud point extraction coupled with flame atomic absorption spectrometry - Sadaf Sadia Arain; Tasneem Gul Kazi; Jamshed Bashir Arain; Hassan Imran Afridi; Atif Gul Kazi; Syeda Nasreen; Kapil Dev Brahman (Environmental Science and Pollution Research, 2014)

A Proposed Methodology for In Vitro Evaluation of Bitterness in Drug Solutions and In Vitro Drug Release Samples - Kapil Dev; Vandana Kharb; Anupama Singh; Vikas Anand Saharan; Hemant Jadhav; Suresh Purohit (Journal of Pharmaceutical Innovation, 2014)

Interaction Between Essential Elements Selenium and Zinc with Cadmium and Mercury in Samples from Hypertensive Patients - Hassan Imran Afridi; Tasneem Gul Kazi; Farah Naz Talpur; Atif Kazi; Sadaf Sadia Arain; Salma Aslam Arain; Kapil Dev Brahman; Abdul Haleem Panhwar; Naeemullah; Mariam Shezadi; Jamshed Ali (Biological Trace Element Research, 2014)

Interaction Between Selenium and Mercury in Biological Samples of Pakistani Myocardial Infarction Patients at Different Stages as Related to Controls - Hassan Imran Afridi; Tasneem Gul Kazi; Farah Naz Talpur; Atif Kazi; Sadaf Sadia Arain; Salma Aslam Arain; Kapil Dev Brahman; Abdul Haleem Panhwar; Naeemullah (Biological Trace Element Research, 2014)

Evaluation of Calcium and Magnesium in Scalp Hair Samples of Population Consuming Different Drinking Water: Risk of Kidney Stone - Abdul Haleem Panhwar; Tasneem Gul Kazi; Hassan Imran Afridi; Haffeezur Rehman Shaikh; Salma Aslam Arain; Sadaf Sadia Arain; Kapil Dev Brahman (Biological Trace Element Research, 2013)

Investigation of Alteration in the Levels of Iron and Copper in Scalp Hair Samples of Patients Having Different Types of Viral Hepatitis - Salma Aslam Arain; Hassan Imran Afridi; Tasneem G. Kazi; Farah Naz Talpur; Faheem Shah; Sadaf Sadia Arain; Abdul Haleem Panhwar; Kapil Dev Brahman (Biological Trace Element Research, 2013)

Polymorphic Variation of CYP1A1 and CYP1B1 Genes in a Haryana Population - Shiv Kumar Giri; Anita Yadav; Anil Kumar; Kapil Dev; Sachin Gulati; Ranjan Gupta; Neeraj Aggarwal; Sanjeev Kumar Gautam (Biochemical Genetics, 2013)

Agrobacterium tumefaciens-mediated in planta seed transformation strategy in sugarcane - Subramanian Mayavan; Kondeti Subramanyam; Muthukrishnan Arun; Manoharan Rajesh; Gnanajothi Kapil Dev; Ganeshan Sivanandhan; Balusamy Jaganath; Markandan Manickavasagam; Natesan Selvaraj; Andy Ganapathi (Plant Cell Reports, 2013)

Correlated Changes in Body Melanisation and Mating Traits of Drosophila melanogaster: A Seasonal Analysis - Kapil Dev; Jyoti Chahal; Ravi Parkash; Sudhir Kumar Kataria (Evolutionary Biology, 2013)

A promising approach on biomass accumulation and withanolides production in cell suspension culture of Withania somnifera (L.) Dunal - Ganeshan Sivanandhan; Gnanajothi Kapil Dev; Murugaraj Jeyaraj; Manoharan Rajesh; Manickam Muthuselvam; Natesan Selvaraj; Markandan Manickavasagam; Andy Ganapathi (Protoplasma, 2013)

Agrobacterium-mediated transformation of the medicinal plant Podophyllum hexandrum Royle (syn. P. emodi Wall. ex Hook.f. & Thomas) - Manoharan Rajesh; Murugaraj Jeyaraj; Ganeshan Sivanandhan; Kondeti Subramanyam; Thankaraj Salammal Mariashibu; Subramanian Mayavan; Gnanajothi Kapil Dev; Vasudevan Ramesh Anbazhagan; Markandan Manickavasagam; Andy Ganapathi (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Increased production of withanolide A, withanone, and withaferin A in hairy root cultures of Withania somnifera (L.) Dunal elicited with methyl jasmonate and salicylic acid - Ganeshan Sivanandhan; Gnanajothi Kapil Dev; Murugaraj Jeyaraj; Manoharan Rajesh; Annavi Arjunan; Manickam Muthuselvam; Markandan Manickavasagam; Natesan Selvaraj; Andy Ganapathi (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Analysis of cadmium, nickel, and lead in commercial moist and dry snuff used in Pakistan - Tasneem Gul Kazi; Sadaf Sadia Arain; Hassan Imran Afridi; Naeemullah; Kapil Dev Brahman; Nida Fatima Kolachi; Moina Akhtar Mughal (Environmental Monitoring and Assessment, 2013)

Seasonal variations in the mating-related traits of Drosophila melanogaster - Kapil Dev; Jyoti Chahal; Ravi Parkash (Journal of Ethology, 2013)

Shifting clinal patterns of stress resistance traits in Drosophila ananassae - Jyoti Chahal; Kapil Dev (Evolutionary Ecology, 2013)

Starvation Resistance in a Stenothermal Species from the Indian Subcontinent: Mechanistic Basis of Clinal Variation - Jyoti Chahal; Ravi Parkash; Kapil Dev (Evolutionary Biology, 2013)

Effect of culture conditions, cytokinins, methyl jasmonate and salicylic acid on the biomass accumulation and production of withanolides in multiple shoot culture of Withania somnifera (L.) Dunal using liquid culture - Ganeshan Sivanandhan; Manoharan Rajesh; Muthukrishnan Arun; Murugaraj Jeyaraj; Gnanajothi Kapil Dev; Annavi Arjunan; Markandan Manickavasagam; Manickam Muthuselvam; Natesan Selvaraj; Andy Ganapathi (Acta Physiologiae Plantarum, 2013)

Expression of Transcriptional Factor Genes (Oct-4, Nanog, and Sox-2) and Embryonic Stem Cell-Like Characters in Placental Membrane of Buffalo (Bubalus bubalis) - Kapil Dev; Shiv Kumar Giri; Anil Kumar; Anita Yadav; Birbal Singh; Sanjeev Kumar Gautam (The Journal of Membrane Biology, 2012)

Reversal of propoxur-induced impairment of memory and oxidative stress by 4′-chlorodiazepam in rats - Kapil Dev Mehta; Gobind Rai Garg; Ashish K. Mehta; Tarun Arora; Amit K. Sharma; Naresh Khanna; Ashok K. Tripathi; Krishna K. Sharma (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)